Big data analytics in the insurance market - Sood, Kiran; Balusamy, Balamurugan; Grima, Simon; Marano, Pierpaolo (Bingley, U.K. : Emerald Publishing Limited, 2022)
Big Data Analytics in the Insurance Market is an industry-specific guide to creating operational effectiveness, managing risk, improving financials, and retaining customers. This book will be a'must' for people seeking to broaden their knowledge of big data concepts and their real-world applications, particularly in the field of insurance. The insurance industry is largely dependent on data, and the advent of Big Data and analytics represents a major advance with tremendous potential. Yet clear, practical advice on the business side of analytics is lacking. This book fills the void with concrete information on using Big Data in the context of day-to-day insurance operations and strategy. This book an invaluable resource for any insurance professional from practitioners and policymakers working at insurance companies, to undergraduate and graduate students of economics management, and finance. Providing high quality academic research, ESFIRM provides a platform for authors to explore, analyse and discuss current and new financial models and theories, and engage with innovative research on an international scale.
Chapter 1. Cyber Security and Data Privacy in the Insurance Market / Priti Rani Rajvanshi, Taranjeet Singh, Deepa Gupta, and Mukul Gupta -- Chapter 2. Comparative predictive performance of BPNN and SVM for Indian Insurance Companies / Jasleen Kaur and Payal Bassi -- Chapter 3. Big Data Analytics for Credit Card Fraud Detection Using Supervised Machine Learning Models / Yakub Kayode Saheed, Usman Ahmad Baba, and Mustafa Ayobami Raji -- Chapter 4. Decision Making Optimization in Insurance market using Big Data Analytics-Survey / Manish Bhardwaj and Shivani Agarwal -- Chapter 5. Bigdata Analytics Adoption In The Indian Insurance Industry: Challenges & Solutions / Maryam Saeed and Noman Arshed -- Chapter 6. Sustainable Economic Growth with Big Data Analytics / Shivani Vaid -- Chapter 7. Insurance Automotive Application Using Edge Computing / Kamal Gulati and Pallavi Seth -- Chapter 8. Big Data Analytics Application in the Indian Insurance Sector / Shikha Sharma, Manju Dahiya, and Simon Grima -- Chapter 9. Big Data: A Disruptive Innovation in the Insurance Sector / Aradhana Rana, Rajni Bansal, and Monica Gupta -- Chapter 10. Recent Trends and Inflows of Foreign Direct Investment in India: With a Specific Reference to the Insurance Sector / Samridhi Tanwar and Surbhi Bhardwaj -- Chapter 11. Employing Bibliometric Analysis to identify emerging Technologies in the Insurance Industry / Akhil M P -- Chapter 12. The Impact of Big Data Technology on the Advancement of the Insurance Industry / Teena Pareek -- Chapter 13. Can Central bank digital currency increase financial inclusion? Arguments for and against / Peterson K Ozili -- Chapter 14. Application of Machine Learning for Fraud Detection- A Decision Support System in the Insurance Sector / Jyoti Verma -- Chapter 15. The role and significance of data protection in risk management practices in the insurance market / Sonal Trivedi and Reena Malik -- Chapter 16. Emerging Technologies in the Insurance Market / Jagjit Singh Dhatterwal, Kuldeep Singh Kaswan, Pretty, and Balamurugan Balusamy -- Chapter 17. The Role of Artificial Intelligence in the Insurance Industry of India / Vimal Sharma and Deepak Sood.
Includes bibliographical references and index.
Print version record.
Keywords: Insurance -- Data processing; Insurance companies -- Data processing; Big data; Business & Economics -- Insurance -- General; Insurance & actuarial studies